Monocarboxylate transporter mediated uptake of moxifloxacin on human retinal pigmented epithelium cells. (1st September 2013) - Barot, Megha; Gokulgandhi, Mitan R.; Agrahari, Vibhuti; Pal, Dhananjay; Mitra, Ashim K.
Abstract Objectives This work was aim to determine in vitro interaction of moxifloxacin with monocarboxylate transporter (MCT) using a human retinal pigment epithelium cells (ARPE‐19). Methods In vitro moxifloxacin uptakes were performed at 37°C across ARPE‐19 cells. Concentration‐dependent uptake of moxifloxacin was performed to delineate moxifloxacin kinetics with MCT. Effects of MCT substrates, MCT inhibitors, pH and metabolic inhibitors on moxifloxacin uptake were conducted to delineate mechanism of moxifloxacin influx via MCT. Key findings Moxifloxacin uptake was found to exhibit saturable kinetics (Km = 1.56 ± 0.32 μm and Vmax = 0.58 ± 0.16 μm/min/mg protein). Higher uptake of moxifloxacin was observed at acidic pH. MCT substrates such as salisylic acid, ofloxacin and L‐lactic acid significantly inhibited the uptake of moxifloxacin. Furthermore, moxifloxacin uptake was significantly reduced in the presence of metabolic and MCT inhibitors. Overall, this study demonstrated an interaction of moxifloxacin with Na+ and H+‐coupled transporter, most likely MCT1. Conclusions Apart from the lipophilicity, we anticipate that lowest vitreal half‐life of intravitreal moxifloxacin compared with other fluoroquinolones may be due to its interaction with MCT. This information might be crucial in clinical settings and can be further explored to improve vitreous half‐life and therapeutic efficacy of moxifloxacin.